Can Coastal Upwelling Trigger a Climate Mode? A Study on Intraseasonal‐Scale Coastal Upwelling Off Java and the Indian Ocean Dipole - T. Horii; E. Siswanto; I. Iskandar; I. Ueki; K. Ando (Geophysical Research Letters)
Abstract Coastal upwelling along the southern coast of Java brings cold and nutrient‐rich subsurface water to the surface. We explored whether the upwelling could trigger the onset of the Indian Ocean Dipole (IOD) by supplying cold water to the southeastern tropical Indian Ocean. We used satellite‐based daily chlorophyll‐a concentration (Chl‐a) data during 2003–2020 as a proxy of the coastal upwelling. We focused on first Chl‐a bloom that occurred in April‐June, the onset phase of the positive IOD (pIOD). We found that the timing and strength of the upwelling signals were significantly correlated with the subsequent IOD peaks. We diagnosed processes associated with the upwelling affecting sea surface temperature (SST) in the southeastern Indian Ocean. Results indicate that after the cold‐water upwelling south of Java, westward surface temperature advection plays a role in anomalously cooling the SST in the southeastern Indian Ocean and setting a favorable condition for the subsequent pIOD development.